2015
DOI: 10.5860/rusq.55n2.132
|View full text |Cite
|
Sign up to set email alerts
|

Adult Readers’ Advisory Services through Public Library Websites

Abstract: Public libraries have implemented Readers’ Advisory (RA) services and outreach efforts online in a variety of formats, ranging from one-way communications such as book club announcements and reading lists to interactions with individual patrons about their reading preferences. While the literature contains numerous case studies describing online RA activities and extensive recommendations for practice, what is lacking is a broad, generalizable picture of what percentage of libraries are offering online RA, wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Foreign scholars and practitioners highlight some issues of creation and operation of libraries' websites. In particular, they study issues about site content management solutions (S. Conrad, C. Stevens [13] and J. Buell, M. Sandford [14]); ease of use of a university library site (E. Azadbakht, J. Blair, L. Jones [15]); consulting services on a site (S. Burke and M. Strothmann [16]); mobile applications and mobile sites (D. Potnis, R. Regenstreif Harms, E. Cortez [17] and N. Arroyo-Vázquez, J.-A. Merlo-Vega [18]).…”
Section: Introductionmentioning
confidence: 99%
“…Foreign scholars and practitioners highlight some issues of creation and operation of libraries' websites. In particular, they study issues about site content management solutions (S. Conrad, C. Stevens [13] and J. Buell, M. Sandford [14]); ease of use of a university library site (E. Azadbakht, J. Blair, L. Jones [15]); consulting services on a site (S. Burke and M. Strothmann [16]); mobile applications and mobile sites (D. Potnis, R. Regenstreif Harms, E. Cortez [17] and N. Arroyo-Vázquez, J.-A. Merlo-Vega [18]).…”
Section: Introductionmentioning
confidence: 99%
“…5 Despite focused professional attention, this trend is still in early stages; Burke and Strothmann recently found that although librarians who have experimented with online RA receive positive feedback from patrons and improve the quality of their RA service, "libraries that offer robust online RA services remain a minority," with only 17.6 percent of public libraries in their study's sample having a RA page on their website. 6 A prominent recent example is the My Librarian program, launched by the Multnomah County Library after extended research, a successful initiative to bridge the gap between online patrons and readers' advisors. House writes that "My Librarian takes a big step toward humanizing the online library experience."…”
Section: Recent Trends In Ra Educationmentioning
confidence: 99%